2001
DOI: 10.1097/00124784-200107020-00009
|View full text |Cite
|
Sign up to set email alerts
|

Interim Assessment of a Community Intervention To Improve Breast and Cervical Cancer Screening among Korean American Women

Abstract: Breast and cervical cancer screening practices are suboptimal among Korean American women. A community intervention program was launched in 1996 to improve breast and cervical cancer screening among Korean American women in Alameda County, California. After 18 months, interim program assessment revealed that mammograms improved, but Pap smears, breast self-examinations, and clinical breast examinations did not change significantly. However, results were similar for the control county probably because the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Although two articles (Kim and Menon 2009; Kim et al 2010) tested the same intervention program (‘Go Early’), the articles were considered as separate intervention tests because they reported on studies that had different participants, study periods, and designs. However, two intervention articles for promoting a breast and cervical cancer screening program (‘Health is Strength’) were regarded as one study despite the recruitment of different participants during different study periods because the former article was considered as an interim assessment study for the latter article (Moskowitz et al 2007; Wismer et al 2001). Thus, data are presented for 16 unique intervention tests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although two articles (Kim and Menon 2009; Kim et al 2010) tested the same intervention program (‘Go Early’), the articles were considered as separate intervention tests because they reported on studies that had different participants, study periods, and designs. However, two intervention articles for promoting a breast and cervical cancer screening program (‘Health is Strength’) were regarded as one study despite the recruitment of different participants during different study periods because the former article was considered as an interim assessment study for the latter article (Moskowitz et al 2007; Wismer et al 2001). Thus, data are presented for 16 unique intervention tests.…”
Section: Resultsmentioning
confidence: 99%
“…The Cognitive-Social Health Information Processing Model guided a study related to tobacco cessation (Fang et al 2006). Community-based Participatory Research (CBPR) guided two studies (Kim et al 2009; Song et al 2010; Kim and Sarna 2004), community-sensitive research principles directed one study (Moskowitz et al 2007; Wismer et al 2001), and the Quality Health Outcome Model guided one study (Sin et al 2005). …”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that women who are unable to speak or read English cannot successfully navigate the healthcare system to schedule their appointments and/or communicate with healthcare professionals (8). However, although Korean women face considerable barriers to screening, few programs have been designed specifically for this population subgroup (12,16).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, an intervention on cognitive factors, which provided Korean immigrant communities with education and information about breast cancer screening, failed to make a significant improvement in screening rates compared to the control group. 14 Furthermore, an intervention intended to eliminate financial barriers, which provided various sub-Asians, including Koreans, with free mammograms, was not successful in obtaining improved screening rates. 13 Not until Korean immigrant women's perceptions of breast cancer screening are checked into precisely and interpreted accurately will improving the breast cancer screening rate be successful.…”
mentioning
confidence: 99%